The Influence of Abiotic Factors on The Diversity and Abudance of Mangrove Crabs (Scylla spp.) in Blok Bedul Alas Purwo National Park Mangrove Forest - Rina Sugiarti Dwi Gita; Sudarmadji Sudarmadji; Joko Waluyo (Jurnal ILMU DASAR, 2015)
The purpose of this study was to determine the diversity, abundance and abiotic factors influence the diversity and abundance of mud crab (Scylla spp.) In mangrove forests Blok Bedul Alas Purwo National Park. This research method uses descriptive quantitative method. Diversity is calculated by using the formula of Shannon Wiener, mangrove crab abundance is calculated using the formula abundance Kreb whereas the method of analysis using simple linear regression. The data used in this research is data such as the number and type of biotic mud crabs and data abiotic form of measurement of temperature, pH, salinity, substrate type, and the tide. This study shows the results include mangrove crab species diversity index of every observation stations in the mangrove forests Blok Bedul Alas Purwo National Park is H '= 0.315 showing that the level of diversity in every station is low. The abundance of mud crabs in the mangrove forests Blok Bedul Alas Purwo National Park is 0.0011 individuals / m² which showed that the level of abundance at relatively low research station. Results of the analysis of the influence of abiotic factors on the diversity and abundance of mud crabs in mangrove forests Blok Bedul National Park Alas Purwo not significant (p> 0.05) the diversity and abundance of mangrove crab.   Keywords : abiotic factors , abundance , diversity , mud crab , regression